Gender and Islamic Inheritance Law: Reassessing Quranic Interpretations of Women’s Inheritance Rights - Fatima Essop (Mazahib, 2026)
This article challenges dominant interpretations of Islamic inheritance law by advancing alternative readings of Qur’anic texts that produce more equitable outcomes for female heirs. Although gender justice in Islamic marriage and divorce law has received extensive scholarly attention, inheritance law (mirāth) remains comparatively underexamined, partly because it is widely perceived as immutable. This study demonstrates that inheritance rulings have historically been subject to scholarly disagreement and ijtihād since the era of the Prophet’s Companions, including in the two decisions of ʿUmar (al-ʿUmariyyatān). The article traces three stages in the development of Islamic inheritance law: the initial bequest system, the introduction of fixed Qur’anic inheritance shares, and later restrictions on bequests. It critically examines whether the bequest verses (Q2:180–182) and the widow verse (Q2:240) were abrogated by later inheritance verses. Drawing on the minority yet jurisprudentially rigorous views of Abū Muslim al-Iṣfahānī and Fakhr al-Dīn al-Rāzī, the article argues against abrogation and contends that the hadith “no bequest to an heir” lacks sufficient authority to override Qur’anic provisions. It further argues that alternative hermeneutical approaches can enhance gender equity while remaining faithful to the Qur’an’s principles of justice